Algorithms - ESA 2011 19th Annual European Symposium, Saarbrücken, Germany, September 5-9, 2011. Proceedings - Demetrescu, Camil; Halldórsson, Magnús M. (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 19th Annual European Symposium on Algorithms, ESA 2011, held in Saarbrücken, Germany, in September 2011 in the context of the combined conference ALGO 2011. The 67 revised full papers presented were carefully reviewed and selected from 255 initial submissions: 55 out of 209 in track design and analysis and 12 out of 46 in track engineering and applications. The papers are organized in topical sections on approximation algorithms, computational geometry, game theory, graph algorithms, stable matchings and auctions, optimization, online algorithms, exponential-time algorithms, parameterized algorithms, scheduling, data structures, graphs and games, distributed computing and networking, strings and sorting, as well as local search and set syste